DETERMINAN NILAI PERUSAHAAN DI BURSA EFEK INDONESIA - Anthony Holly (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2018)
The aim of the study is to assess determinant of firm value as profitability, dividend policy, firm size and liquidity for manufacturing companies listed in Indonesia Stock Exchange in 2010-2014. This study using manufacturing companies listed in Indonesia Stock Exchange as sample. Sample selected by purposive sampling method. Sample size generated by this method is 14 companies. Data type used in this study is quantitative data. Data souce in this study is secondary data. The data were then analyzed using multiple linier regression analysis to analysis dependent variable, Firm value (TQ), and independent variable such as profitability, dividend policy, firm size and liquidity.The research results revealed that profitability, dividend policy and liquidity have positive and significant effect to firm value. However other firm size has positive but no significant effect to firm value.